Eksistensi Penyidik Tindak Pidana Pemilu Secara Terpadu Oleh Bawaslu - Mahu, Syarfudin; Pasalbessy, John Dirk; Wadjo , Hadibah Zachra (Publikasi Indonesia, 2025)
Free, honest and fair elections are indicators of a mature democratic country. To guarantee freedom, honesty and justice, administrative and legal instruments are needed that can guarantee the security of every stage of the general election process. One of them is the role of Election Crime Investigators in ensuring security and prosecuting violations that have criminal elements according to the law. Sentra Gakkumdu as a center for handling election crimes under one roof in an integrated manner between Bawaslu, Investigators and Prosecutors aims to align perceptions and patterns of handling election crimes. Technically, the mechanism and procedures for investigating election crimes are carried out by Investigators at the Sentra Gakkumdu which begins with the transfer of findings or reports that are election crimes from Bawaslu according to their level. Handling of election crimes at the Regional Bawaslu (Province and Regency/City) and Bawaslu at the Central level refers to the Election Law and is technically regulated in Perbawaslu No. 7 of 2022 and Perbawaslu 3 of 2023, and also the Criminal Procedure Code if otherwise specified in the Election Law. The purpose of this article is to examine and analyze the obstacles/constraints faced by investigators handling election crimes in an integrated manner through regional Bawaslu. This research is a normative legal research. The type of research is descriptive analysis. Data and supporting information are then identified and then systematized for interpretation and arguments are given to obtain conclusions on the problem. Gakkumdu as a center for law enforcement activities for Election Crimes was formed with the hope of bringing a fair, transparent, and accountable election process in the context of law enforcement for election crimes. However, in practice there are still shortcomings or obstacles, namely legal factors including: short handling time, overlapping authority between investigators and Bawaslu who are members of the Gakkumdu Center, limited authority of the Gakkumdu Center to present witnesses, reports or findings delegated by election supervisors to the Gakkumdu Center sometimes cannot be followed up by investigators because they do not meet formal or material requirements or are not election crimes, law enforcement factors including non-compliance with regulations, sectoral egos, facilities and infrastructure factors, community factors, and cultural factors.